Physiotherapy and its service in Nepal: implementation and status reported from facility surveys and official registers - Nishchal Ratna Shakya; Nistha Shrestha; Gillian Webb; Hellen Myezwa; Biraj Man Karmacharya; Ann-Katrin Stensdotter (BMC, 2024)
Abstract Background Physiotherapy is a growing profession in Nepal. Despite efforts to promote strengthening and development, there are still challenges in providing equitable access and availability to services, particularly in underserved areas. Updated information is needed to address challenges to provide proper planning for resource allocation. Objective To assess implementation of physiotherapy services and to explore plans, policies and the general status of physiotherapy in Nepal. Method Implementation was assessed with a cross-sectional survey conducted in Province III containing closed-ended questions addressing physiotherapy services, human resources, charging and record-keeping systems, and accessibility. Stratified purposive sampling was used to select eligible facilities from the list of Department of Health Services. Official records were explored through visits to governing institutions and by reviews of registers and reports to obtain data and information on status, plans and policy. Results The survey included 25 urban and 4 rural facilities, covering hospitals and rehabilitation centres; both public (37.9%) and non-public (62.1%). Most facilities (79.3%) employed physiotherapists with bachelor's degrees. Average number of visits were 29.55 physiotherapy outpatients and 14.17 inpatients per day. Patient records were mainly paper based. Most (69%) used the hospital main card, while others (31%) had their own physiotherapy assessment card. Most referrals came from doctors. The most offered services were musculoskeletal, neurological, and paediatric physiotherapy. Daily basis charging was common. A single visit averaged 311 Nepalese rupees ≈ 2.33 US$. Convenience for persons with disabilities was reported as partial by 79% of outpatient departments. Official register data showed 313 master's and 2003 bachelor's graduates. Six colleges offered physiotherapy bachelor's degree, whereof one also offered a master's program. Government records revealed significant progress in physiotherapy in Nepal. Conclusion The study highlights variations in physiotherapy services within a province owing to type, size and location, but also unwarranted variations. Despite the progress, implementation of physiotherapy services in the perspective of official records imply a need of systems for proper planning and monitoring. Physiotherapy provision in underserved areas warrants further attention.